Rethinking rhythm in language and music :|can duration prime rhythm in metrical speech? - Tokaç, Züheyra. (Thesis (M.A.)-Bogazici University. Institute for Graduate Studies in the Social Sciences, 2019., 2019)
Rhythmic qualities of languages have been explored and discussed primarily in relation to the much-debated proposal of rhythm classes. Moreover, research on linguistic rhythm has been led by two premises: isochrony and stress. Predominated by a limited set of languages, research in this area fell short of examining remaining languages in compatible ways. The present study aims at taking an alternative approach by building its hypotheses in a language-specific way. As native speakers’ perception of linguistic rhythm becomes most evident in their metrical speech, Turkish poetic meters were examined to identify possible constituents of rhythm in Turkish. Based on a poetic meter that creates rhythmicality through an organization of closed and open syllables, this study examines phonemic duration between vowels of subsequent syllables as such a candidate. Experiment 1 explores the ways in which musical primes with long- and short-interval pulses can prime metrical structure in bisyllabic and trisyllabic linguistic stimuli. Results suggest primes with solely durational contrasts cannot prime the hypothetical durational relationships in linguistic stimuli but can prime syllable number under certain conditions. However, primes with intensity accents were successful in priming syllable number and syllable structure in bisyllabic nonwords, although independently. Experiment 2 examines whether priming syllable number and duration can be differentiated and yields null results. Taken together, results lean towards an understanding of rhythm in Turkish that is based on syllable number while not also rejecting a duration-based alternative.
Keywords: Music -- Psychological aspects.; Rhythm.